Yargı kararları ışığında yabancı uyruklu gerçek kişilerin Türkiye’de miras yoluyla taşınmaz edinmesi - Oruç, Murat; Kulaklı, Emrah (İstanbul Medipol Üniversitesi, 2021)
Türk Medeni Kanunu m. 577 vd. hükümleri, bir kimsenin mirasçı veya vasiyet alacaklısı olabilmesi için gerekli şartları belirlemektedir. Bununla birlikte, yabancı uyruklu gerçek kişilerin Türkiye’de taşınmaz edinebilmelerine ilişkin Tapu Kanunu m. 35’te özel bir düzenleme mevcuttur. Bu hükümde yapılan 2003 tarihli değişiklik sonrası yabancı uyruklu gerçek kişilerin Türkiye’de taşınmaz edinebilmelerine ilişkin şartlar köklü değişikliklere uğramıştır. Bu bağlamda çalışmamızda öncelikle TMK hükümleri çerçevesinde mirasa ehil olmanın şartları genel olarak açıklanacaktır. Sonrasında, konumuzun esasını teşkil eden yabancı uyruklu gerçek kişilerin Türkiye’de taşınmaz mal edinebilmelerini düzenleyen Tapu Kanunu m. 35 hükmü, 2003 yılı değişikliği öncesi ve sonrası olacak şekilde ele alınacak, mülkiyet ve miras hakkı bağlamında hukukî sorun ortaya koyulacaktır. Konuya ilişkin Yargıtay, Anayasa Mahkemesi ve Avrupa İnsan Hakları Mahkemesi içtihatları çerçevesinde yapılacak değerlendirmelerin ardından sonuç kısmında birtakım tespit ve kanaatlerimize yer verilecektir.

Article 577 and the subsequent provisions of the Turkish Civil Code set forth the requirements, which are required for a person to be an inheritor or a receiver due to testament. In the meantime, there is a private regulation under Article 35 of the Land Registry Law with regards to the acquisition of immovable property of the real persons, who are the foreign national, in Turkey. The requirements for the acquisition of the immovable property of the foreign real persons in Turkey have undergone to a fundamental changes after the amendment, which was made in 2003 under the mentioned provision. In this regard, the requirements for the capacity of succeeding will initially be presented in a general frame within the scope of the related provisions of the Turkish Civil Code in this paper. Afterwards, Article 35 of the Land Registry Law, which sets forth the acquisition requirements of the immovable property of the foreign real persons in Turkey constituting the basis of our subject, will be taken up with all details including the circumstance before and after the amendment dated 2003; the legal question will be put down to the fact in the context of the right of property and the right of succession. Following to the submission of our legal evaluations within the scope of the precedent decisions of the Supreme Court, the Constitutional Court and European Court of Human Rights relating to the matter; some of our determinations and legal opinions will be presented at the part of conclusion.
Acquisition of immovable property of real persons, who have foreign nationality, in Turkey by inheritance in consideration of judicial decisions
Keywords: Miras Yoluyla Taşınmaz Edinme; Yabancı Uyruklu Gerçek Kişi; Mülkiyet Hakkı; Temel Haklar; Karşılıklılık (Mütekabiliyet); Acquisition of the Immovable Property by Inheritance; Real Person Who Has Foreign Nationality; Right of Property; Fundamental Rights; Reciprocity